The effect of LH supplementation to the GnRH antagonist protocol in advanced reproductive ageing women: a prospective randomized controlled study. (9th September 2015) - Younis, Johnny S.; Izhaki, Ido; Ben‐Ami, Moshe
Summary: Objective: Although the fundamental significance of both LH and FSH for adequate ovarian folliculogenesis and steroidogenesis has been extensively discussed, the clinical implication of recombinant (r) LH to rFSH for ovarian stimulation employing the GnRH antagonist protocol remains to be elucidated. The aim of this prospective randomized controlled study was to explore whether rLH supplementation to rFSH following GnRH antagonist has an added value to the late follicular ovarian steroidogenesis in the advanced reproductive aged women. Design and Subjects: Sixty‐three consecutive infertile women above 35 years of age and/or with a previous low ovarian response admitted for IVF/ICSI treatment were prospectively randomized. Women in the study and control groups were similarly treated employing the rFSH 300 IU/day and the flexible GnRH antagonist 0·25 mg/day protocol. On the day of antagonist initiation, rLH 150 IU/day was added only to the study group and continued till the hCG day. Results: Serum E2 level on hCG day did not significantly differ between the study and control groups, corresponding to 1268 ± 1006 and 1113 ± 669 pg/mL, respectively ( P = 0·9). In the study group, the duration of GnRH antagonist administration was significantly lower than the control group corresponding to 5·0 ± 1·5 to 4·0 ± 1·5 days, respectively ( P < 0·05). The total dosage of rFSH administration did not differ between the two groups. Conclusions: rLH supplementation to rFSH following GnRH antagonist administration employing the flexible protocol does not seem to significantly augment serum E2 level on the day of hCG administration in the advanced reproductive ageing women. This suggests that endogenous serum LH levels following GnRH antagonist initiation are sufficient for adequate late follicular ovarian steroidogenesis in this setting.